Counselling as Moral Conflict: Making the Disintegration Positive - Hague, William J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The fact that counselling cannot truly be value free is generally accepted; the pendulum of developmental psychology is, in fact, swinging back to intense interest in "moral development" and "value clarification". As counsellors, we have a special opportunity to make this current interest in values more than a mere passing fad. By looking in greater depth at what goes on in moral education — the creative disequilibrium of moral challenge coming from exposure to higher levels of moral thinking — the disturbing consequences of facing up to the contrast between "what is" and "what ought to be" — counselling can take on new dimensions. The practical task of this paper is to look at the implications of moral and value education theory and techniques for counselling, particularly the demand they place on the counsellor to make the process a disintegrative one, leading to reintegration on higher levels ofvalues and humanness.